Experimental investigation of a Diaphragm FPSE design using a novel edge welded bellows-displacer assembly - Ghozzi, Salem Saleh (2017)
The energy conversion process of fossil fuels to electrical power is accomplished using inefficient technologies with negative consequences on human health and environment as well as contributing to depletion of finite natural resources. Therefore, there is currently increased societal pressure to adopt more environmentally sustainable and low carbon solutions. The share of energy derived from renewable sources (solar, wind, biomass, etc.) is projected to increase significantly over the next decades to decarbonise the energy sector. However, to achieve this objective, the heat conversion technologies need to make a step improvement in energy conversion. Stirling engine is considered to operate on the most efficient heat cycle capable of operating on a range of fuels including renewables. This research investigated a novel design of a diaphragm Free-piston Stirling Engine for low temperature power generation in remote and inaccessible regions of the world. The design incorporates a flexible edge welded bellows material to support the displacer and a flat elastomer as a power piston. This mechanical arrangement of the moving parts of the engine eliminates air leakage, mechanical friction of the power piston and cylinder, and low spring losses. A proof-of-concept and a validated mathematical model was developed as part of this project. The mathematical model was based on solving the energy, mass and momentum conservation equations of the working fluid in different parts of the engine. The performance of the engine was evaluated for different design parameters such as temperature, pressure, operating frequency, etc. A proof-of-concept prototype was built and tested under controlled laboratory settings to measure the energy performance. It was demonstrated the proof-of-concept engine can operate successfully at low to medium temperatures (up to 300oC) at atmospheric pressure and frequency of 16Hz. The tests also showed that under sufficient temperature gradient the engine is self-starting. Though the shaft power output was insignificant for the size of the engine, the design and laboratory results have contributed to advancing the technology and its application.